Community Empowerment Through One Village One Product Based on Local Potential of Bukit Payung Village: Pemberdayaan Masyarakat Melalui One Village One Product Berbasis Potensi Lokal Desa Bukit Payung - Rina Susanti; Fifi Alfiah; Mutia Dwi Lestari; Annisa Rahmaini; Rivan Tauhid (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Community empowerment through One Village One Product (OVOP) is the concept of the Bukit Payung Village service team. The OVOP concept plays a role in improving the quality of rural potential. The service activity was carried out in Bukit Payung Village, Bangkinang District, Kampar Regency using three interrelated OVOP principles, the first principle, optimizing local potential in producing a product that is only one and number one, then the principle of development based on independence, creativity and innovation and which lastly able to develop human resources. The form of activity from the service team is in the form of training on the use of cow dung and palm sticks as well as innovation of processed yam fruit. This activity aims to create superior village products and realize prosperity by involving the role of the Bukit Payung Village community. Service activities are carried out using the PRA (Participatory Rurral Appraisal) method with three stages, starting with the preparation stage then implementation and reflection. Service activities that produce 3 products, namely Be Ice Bengkuang, compost and palm sticks. Abstrak Pemberdayaan masyarakat melalui One Village One Product (OVOP) menjadi konsep tim pengabdian Desa Bukit Payung. Konsep OVOP berperan sebagai peningkatan kualitas potensi perdesaan. Kegiatan pengabdian dilaksanakan di Desa Bukit Payung, Kecamatan Bangkinang Kabupaten Kampar menggunkaan tiga prinsip OVOP yang saling berkaitan, prinsip yang pertama, mengoptimalkan potensi lokal dalam menghasilkan suatu produk yang only one and number one, selanjutnya prinsip dalam pengembangan berdasarkan kemandirian, kreatifitas dan inovatif dan yang terakhir mampu mengembangkan SDM . Bentuk kegiatan dari tim pengabdian berupa pelatihan pemanfataan limbah kotoran sapi dan lidi sawit serta inovasi olahan buah bengkuang. Kegiatan ini bertujuan untuk menciptakan produk unggulan desa serta mewujudkan kesejahteraan dengan melibatkan peran masyarakat Desa Bukit Payung. Kegiatan pengabdian dilaksanakan menggunakan metode PRA (Participatory Rurral Appraisal) dengan tiga tahapan, dimulai dengan tahap persiapan kemudian pelaksanaan dan refleksi. Kegiatan pengabdian yang menghasilkan 3 produk yaitu Be Ice Bengkuang, pupuk kompos dan kerajinan piring lidi sawit.